ДӘСТАН ДӨРЕТИЎ ДӘСТҮРИ ҲӘМ «ҚЫРЫҚ ҚЫЗ» - Алламбергенов, К. (SCIENCE and SOCIETY, 2021)
The presentation presents the origin of “Kyryk kiz/Fourty gilrs” dastan, as an unique national folk masterpiece of Karakalpak people. This claim came after analysis of origin, development and evolution of dastan by individual authors and dzhiraw’s presenting style were investigated widely based on above mentioned principles.